Japanese female Kendo practitioners are associated with high radial bone mineral density. Issue 18 (17th September 2017) - Matsui, Daisuke; Watanabe, Isao; Koyama, Teruhide; Ozaki, Etsuko; Kuriyama, Nagato; Mizuno, Shigeto; Watanabe, Yoshiyuki
ABSTRACT: Osteopenia is a condition in which bone mineral density (BMD) is lower than normal. Exercise increases BMD in both the young and adults. This study aimed to compare the radial apparent BMD (aBMD) in Japanese females who are Kendo practitioners (KPs) and those with no regular exercise habits (no-REH). The analysis participants consisted of 45 KPs (mean age: 49.4 years old) and 110 no-REH (mean age: 48.8 years old). Radial aBMD was measured using an ultrasonic bone densitometry system. Radial aBMD in KPs was 196.1 ± 33.9 mg/cm 3, and was 182.9 ± 45.3 mg/cm 3 in no-REH participants. KPs had significantly higher BMD than no-REH participants. In KPs, left radial aBMD was 196.1 ± 33.9 mg/cm 3, and right radial aBMD was 184.5 ± 37.7 mg/cm 3 . The left radius was also significantly higher than the right radius with respect to aBMD in KPs. After adjusting for age, body mass index, menstrual status, parous women and frequency of milk and dairy intake, the odds ratio (OR) of osteopenia associated with no-REH was 6.58 (95% confidence interval (CI): 1.72–25.1) and the prevalence ratio (PR) of osteopenia associated with no-REH was 4.12 (95% CI: 1.23–13.7). Therefore, the Kendo practice may have a protective efficacy for osteopenia in women.